Mid-Borderline Leprosy with Mild Type 1 Reaction in Children: A Case Report - Indraswari, Anindia; Listiawan, Muhammad Yulianto (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Leprosy is a chronic infectious disease caused by Mycobacterium leprae. Cases of leprosy in children are rarely found because of the long incubation period of Mycobacterium leprae. Purpose: To report a case of mid-borderline leprosy with a mild type 1 reaction in a seven-years-old girl patient. Case: A 7-years-old girl patient presented with multiple red and white patches on her face, body, arms, legs, and buttocks since 6 months before. There was no itching, numbness, painr fever. There was no thickening of peripheral nerves and no nerve function impairment. Her grandmother was suspected to have leprosy, but she had never been treated and had already passed away. From the acid fast bacilli (AFB) examination, the bacterial index (BI) was 1+ and the morphological index (MI) was 2%. A serologic test examination was also performed and the result were Immunoglobulin (Ig) G 3716 u/ml and IgG 284 u/ml. The patient got multidrugs therapy for 12 months and after 9 months of treatment, the pre-existing patches became erythematous, thickened, and felt pain when touched, but there was no fever. In the presence of pain, oral ibuprofen was then administered and the patches began to improveDiscussion: Due to the possibility of leprosy reaction, it is important to immediately give prompt treatment to children with type 1 leprosy reaction that is associated with neuritis and leads to deformities. Conclusion: Early diagnosis and therapy for a type 1 leprosy reaction are very important to prevent deformities.